Pollination and fruit set behaviour of aonla (Emblica officinalis) - SINGH, H K; SRIVASTAVA, A K; DWIVEDI, R (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted on variability in fruiting potentiality in aonla (Emblica officinalis Gaertn).The maximumtiuit-retention was recorded under open pollination followed by sibbing and geitonogamy, whereas bagging resulted inno-fruit retention. Improvement in fruit retention under sibbing and open pollination compared with the geitonogamymight be due to the effect of foreign pollen grains having high pollination stimulus. Poor-fruit retention undergeitonogamy and bagging indicated the possibility of self-incompatility in all the aonla cultivars/genotypes.